Molecular epidemiological study of Trichomonas gallinae focusing on central and southeastern Europe - Tuska-Szalay, Barbara; Sipos, Gábor; Takács, Nóra; Kontschán, Jenő; Sándor, Attila D.; Péter, Áron; Berta, Krisztián; Kerek, Ádám; Jerzsele, Ákos; Votýpka, Jan; Hornok, Sándor (Frontiers in Veterinary Science, 2022)
Trichomonas gallinae is a geographically widespread protozoan parasite of birds. In this study, oropharyngeal swab samples were collected in Hungary and Romania from 99 columbiform birds, including 76 feral pigeons (Columba livia domestica: 42 kept for racing, 32 with urban and two with rural habitat), four common wood pigeons (C. palumbus), 16 ring doves (Streptopelia risoria) and three Eurasian collared doves (S. decaocto). These samples were analyzed for the presence of T. gallinae using molecular methods. Racing feral pigeons had significantly higher prevalence of T. gallinae infection than urban feral pigeons. The rate of PCR-positivity was the highest among wood pigeons and ring doves. Based on 18S rRNA gene, T. gallinae was the most heterogenous among racing feral pigeons sampled in a trading-breeding place. Clinical signs were associated with only one 18S rRNA gene subtype. The most divergent 18S rRNA gene subtype, Trichomonas sp. Hu-TG37 clustered with T. canistomae and T. tenax and represents probably a new species. To our knowledge, this is the first report on the genetic diversity of T. gallinae in the southeastern European region. The results suggest that most detected T. gallinae 18S rRNA gene subtypes are not host-specific and do not cause clinical signs. The highest number of 18S rRNA gene subtypes was demonstrated among racing feral pigeons. Significantly more captive than free-living columbiform birds had T. gallinae infection. These data highlight the importance of epizootic monitoring of the genetic diversity and presence of T. gallinae in trading-breeding places of pigeons and doves.